Association between homocysteine and incidence of ischemic stroke in subjects with essential hypertension: A matched case-control study. (3rd October 2015) - Wang, Changyi; Han, Liyuan; Wu, Qunhong; Zhuo, Renjie; Liu, Kui; Zhao, Jinshun; Zhang, Lina; Hao, Yanhua; Fan, Rui; Liu, Yanfen; Li, Runhua; Chen, Zhongwei; et al.
Abstract: Background : To assess the association between total plasma homocysteine (tHcy) and ischemic stroke (IS) in hypertensive subjects in a matched case-control study. Methods : This is a 1:2 matched and population-based case-control study, all of the participants were recruited from the 60 communities in Shenzhen, China. Demographic and socioeconomic characteristics, medical records, lifestyle risk factors and other clinical characteristics were obtained from all of the subjects. The association between tHcy and incidence of IS was analyzed by using conditional logistic regression models. Results : The median values of plasma tHcy were significantly higher in IS subjects than in non-IS subjects, especially in women. After adjusted for the confounding factors in Model 2, compared with the lowest quartile of tHcy, the odds ratios (ORs) and 95% CIs of the highest quartile of tHcy for IS were 0.83 (0.36–1.90) in men, 4.51 (1.29–15.7) in women and 1.31 (0.70–2.47) in the total subjects; the ORs and 95% CIs for IS per 5 μmol/L increase in homocysteine were 1.11 (0.99–1.22), 1.25 (1.03–1.58) and 1.15 (1.01–1.28) in men, women and total subjects, respectively. We observed significant associations in crude model, Model 1 and Model 2 in women for the comparison of tHcy ≥ 15 μmol/L versus < 15 μmol/L. Interaction analysis showed that the association of tHcy with IS was significant in women ( p -interaction = 0.04). Conclusion : This matched case-control study indicates that tHcy may increase the susceptibility to IS in essential hypertension subjects, especially in women. Further large prospective cohort studies are needed to confirm our findings.